Mapping Determinants of Beneficiary Knowledge in TSP: Evidence for Targeted Extension Strategies - Mohanty, Smaranika; Rout, Santosh Kumar; Jayasingh, Debi Kalyan (Indian Journal of Extension Education, 2025)
The study was conducted in 2024 to map the determinants of the knowledge levels of tribal beneficiaries enrolled under the Tribal Sub Plan (TSP) programme. A sample of 240 tribal farmers was considered as respondents under multi-stage random sampling, followed by a personal interview with a structured questionnaire for executing the process of data collection. More than half of the factors expressed a significant relationship with the knowledge level of TSP programme. Factors like education, cosmopoliteness, training participation and extension contact were prominently contributing towards knowledge level, as these, along with other factors, in total managed to elucidate about fifty-six per cent of the variation caused in knowledge level.
Keywords: Knowledge level; Socio-personal factors; Tribal Sub Plan; Tribals; Correlation; Regression